Microstructure and adherence of vitreous enamel to low carbon steel. (1st January 2011) - Zhang, Aiwen; Jiang, Zhengyi; Jiao, Sihai; Wei, Dongbin
The microstructure and adherence of vitreous enamel to low carbon steel substrate with different compositions were evaluated by using optical microscopy, scanning electron microscopy and the bending test method. The condition of the bubbles, the fish-scaling resistance, and the adherence strength were also analysed by microscopic methods. The results show that the microstructures of the enamel layers are similar for the two steels, while the addition of titanium and vanadium to the steel degrades the adherence. The mechanism of enamel-steel interface adherence could be explained as mainly mechanical interlocking, chemical bonding subsequent to a series of chemical reactions. Fe-rich dendrites can only be found in the bubbles located inside the interface transit zone.